Economic thoughts of Amartya Sen - Inderjeet Singh; Anil Kumar Thakur (Published on behalf of the Indian Economic Association by Regal Publications, 2012)
Papers presented at the 93rd Annual Conference of the Indian Economic Association, held at Punjab University during 27-29 December 2010.